Kepuasan Konsumen Pada Usaha Cafe Encasa Di Kelurahan Malalayang Satu Timur Kota Manado - Deba, Jarot; Baroleh, Jenny; Wariki, Barce (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine customer service satisfaction at the Encasa Café business in Malalayang Satu Timur Village, Malalayang District, Manado City. The research was conducted for 2 months from June to July 2023. The research place was held at Café Encasa which is located at Jalan Krida, Malalayang Satu Timur Village, Malalayang District, Manado City. The data collected in this study were obtained through primary data and secondary data. The sample was determined using accidental sampling technique as many as 30 respondents. The data analysis method used is descriptive data analysis, using Likert Scale measurements. Based on the results of the study, it can be concluded that customer satisfaction at Café Encasa in Malalayang Satu Timur Village, Manado City is 72.8% or consumers are in the satisfied category. The highest category in the catchability variable with a value of 80.9% with a very satisfied category, for the lowest category with a value of 66.2% with a satisfied category is in the reliability variable.